A comparative analysis of fixed income unit trust funds versus equity unit trust funds in Malaysia - Nur Adiana Hiau Abdullah; Aminah Shari (Penerbit USM, 2019)
This study examines the performance of fixed income and equity unit trust funds from 2006 to 2012. A total of 31 fixed income and 57 equity funds are evaluated by using the Treynor ratio, Sharpe ratio and Jensen alpha. Results indicate that fixed income funds outperform the market and the Maybank 12-month fixed deposit rate. Their total risk is higher than the fixed deposit rate but lower than the market whereas the systematic risk is lower than both benchmarks. All equity funds outperform the market although their total risk and systematic risk are lower than the latter. Growth funds have a higher total risk than the market and they have outperformed the market. However, only a few value funds could outperform the market. Jensen alpha shows only a few fixed income and equity funds have a significant positive alpha implying that some of the fund managers are either good in market timing or in selecting unit trust funds. There is a significant difference in the performance of equity and fixed income funds and between growth and value funds versus f ixed income funds. Results of this study could help investors and fund managers to make informed decisions to improve portfolio performance.